Integrasi Pasar Daging Ayam Ras (Broiler) di Pasar Modern Indonesia - Pratiwi, Dita; Andarwangi, Tunjung; Tantriadisti, Shinta; Ulfah, Maria (Politeknik Negeri Lampung, 2023)
Production and consumption of chicken meat in Indonesia continues to increase; however, the development of broiler chicken prices at the consumer level tends to fluctuate. In addition to price fluctuations, there are risks related to chicken weight depreciation, chicken mortality, transportation costs, as well as poorly organized marketing channels and distribution patterns for broiler chickens. The distribution pattern of broiler chicken meat is closely related to market integration. Market integration is one of the characteristics of an efficient market, where strong integration means that price information at various market levels is well communicated. Therefore, a study will be conducted to assess the market integration of broiler chicken meat at the farmer and retailer levels in modern markets. The data used in this study will consist of monthly time series data for five years, from January 2018 to December 2022. The study on market integration of broiler chicken meat will employ the Index of Market Connection (IMC) analysis. Based on the IMC value of 5.242 and β2 value of 0.283, it can be concluded that the market integration of chicken meat at the Farmer and Modern Market levels is classified as weak, in the long terms.